Systematic Review of Evidence for Plasma and Peritoneal Lactate as a Diagnostic Test for Surgical Colic. (September 2015) - Cullen, T.E.; Curtis, L.; England, G.C.W.; Burford, J.H.; Freeman, S.L.
Abstract : Reason for performing study: Measurement of lactate in horses with colic has been described for over 20 years. Objectives: To systematically review the evidence on the use of plasma and/or peritoneal lactate as a diagnostic test for identifying surgical colic. Study design: Systematic review. Methods: The primary literature search was conducted in CAB Abstracts (1910–2014), WEB of Science (1950–2014) and MEDLINE (1946–2014) using search terms relating to equine colic. Publications were assessed against inclusion and exclusion criteria, and then reviewed using the QUADAS scoring system. Results: The primary search identified 5508 publications relating to colic; 32 studies related to the use of lactate in the diagnosis of colic, 2 papers met the inclusion criteria and were assessed using QUADAS. Both papers investigated the use of plasma and peritoneal lactate to identify strangulating intestinal lesions. Both were cross‐sectional studies, and together they evaluated a total of 71 horses with confirmed strangulating lesions. Appraisal of the studies using the QUADAS tool was performed. Both papers met QUADAS criteria relating to study design and data analysis, but the QUADAS tool did highlight some limitations in terms of sample and control groups in both papers. Data analysis varied, with one study developing a model to predict the presence of a strangulating lesion, which included peritoneal lactate and other measurements, and the other study assessing optimal predictive values associated with concentrations of peritoneal lactate. Both studies concluded that peritoneal lactate was a more useful diagnostic test than blood lactate. Conclusions: Despite the large numbers of publications reporting use of lactate, only a small number used study designs considered suitable for evaluation of diagnostic test accuracy as proposed by the Cochrane Library. Although the current evidence is limited, there is agreement on the value of peritoneal lactate as a diagnostic test for strangulating intestinal lesions. Ethical animal research:  Not applicable.Sources of funding:  Tom Cullen is a Junior Clinical Training Scholar funded by the School of Veterinary Medicine and Science, University of Nottingham and Oakham Veterinary Hospital. Laila Curtis' PhD studentship is funded by the School of Veterinary Medicine and Science, University of Nottingham.Competing interests:  None declared.